The Influence of The Constructivism Learning Model on The Quality of Learning in Panyabungan District State Elementary School - Defi, Wahyu Fitrina; Febrina, Weli; Rifma, Rifma; Jasrial, Jasrial; Syahril, Syahril (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to investigate the effect of applying the constructivist learning model on the quality of learning. This research was conducted at the Panyabungan Mandailing Natal District Elementary School. The research method used is quantitative, with a causative approach. The population of this study was all 84 teachers spread across 6 public elementary schools in Panyabungan sub-district. The research sample consisted of 35 people, obtained through a stratified proportional random sampling technique. Research data was collected through questionnaires which have been tested for validity and reliability. The analysis technique used is the level of response attainment (TCR) to describe the data, while the analysis requirements tests carried out are the normality test and linearity test. Next, testing the hypothesis is carried out using simple correlation and regression. The research results revealed that the constructivist learning model had a significant effect on the quality of learning by 32.2%. The implications of these findings can be used as a basis for improving the quality of learning in similar schools and making a positive contribution to the development of learning models that suit the contextual needs of education in Indonesia.